Regulação em saúde: limites e possibilidades para resolubilidade da atenção à saúde - Silva, Brisa Ricardo Xavier da (2022)
The National Regulation Policy is a management strategy aimed at organizing the Brazilian health system, improving available resources, qualifying the population's attention and access to health actions and services. The excessive use of referrals is a reality, incisively compromising the increase in waiting lines and delays in diagnoses. Thus, management seeks strategies for the qualification of the access network and health professionals, developing specific public policies that include the support and quality of the service offered to the population. The study aims to analyze the demand for specialized referrals for diagnoses of musculoskeletal disorders within the Family Health Units. In this work, we used the database built by the researcher from the data of referrals available at the center of regulation of health districts III, IV and V. The sample has 642 referrals from users scheduled in the regulation system in the period of February and March 2022. For the study, the information contained in regulated referral forms is considered, which are: sociodemographic data, clinical diagnosis, procedure, risk classification and time of request before the system. It was a cross-sectional, descriptive study with a quantitative approach. The statistical approach involved descriptive data analysis and logistic regression modeling, to evaluate the process of optimizing referrals for possible authorization and execution and, consequently, encouraging the resolvability of the regulatory system. The results show that the regulation system to present effectiveness in its logistical and management context still has many obstacles, since most of the variables had no relevance to the study, showing that our primary network is still very fragile in comprehensive and long-line care. We realized that the decision-making capacity of professionals is greatly influenced by social and economic aspects, which causes greater difficulties in new perspectives on health. Therefore, the study becomes relevant from the moment it demonstrates how the regulatory system suffers consequences from the management of primary care, observing how important it is to invest in strengthening actions for this level of care, given that the change being reached by the public of professionals and users of this level of care, significant changes can be achieved at a specialized level. It is interesting to point out that we have the resources to achieve these facts, all it takes is the restructuring of the sector.